Recycled content cast film
Patent Information
- Application Number
- CN202580024731.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-28
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies make it difficult to effectively utilize high-purity recycled polyolefin materials to manufacture cast films with excellent mechanical and optical properties, especially due to the performance degradation caused by the presence of inorganic residues.
A polymer composition comprising 0.0 wt% to 80.0 wt% of virgin propylene polymer and 20.0 wt% to 100.0 wt% of mixed plastic polypropylene blend is used to optimize the composition of the cast film to balance mechanical and optical properties by controlling the melt flow rate, the proportion of crystal fraction and soluble fraction.
This invention achieves a favorable balance between the mechanical and optical properties of high-purity recycled material cast films, significantly improves the film performance of recycled materials, solves problems that are difficult to solve in existing technologies, and realizes the efficient utilization of recycled materials in cast films.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to cast films containing certain high-purity recycled material grades and having a favorable balance of mechanical and optical properties. Background Technology
[0002] Over the past decade, there has been a growing focus on plastics and the environmental sustainability of their current usage. This has spurred new regulations regarding the disposal, collection, and recycling of polyolefins. Furthermore, several countries are working to increase the proportion of plastic materials recycled rather than sent to landfills.
[0003] In Europe, plastic waste accounts for approximately 27 million tons of waste annually; of this, 7.4 million tons were landfilled in 2016, 11.27 million tons were incinerated (to generate energy), and approximately 8.5 million tons were recycled. Polypropylene-based materials are a particularly prominent issue due to their widespread use in packaging. Considering the enormous volume of waste collected compared to the amount recycled and reintroduced into the flow (only about 30%), the rational reuse of the plastic waste stream and the mechanical recycling of plastic waste still hold great potential.
[0004] Taking the automotive industry as an example, in Europe, the EU's End-of-Life (ELV) Directive stipulates that 85% / 95% of vehicle materials should be recyclable or recoverable. Currently, the recycling rate of automotive parts is significantly lower than this target. On average, vehicles are composed of 9% by weight of plastic, and of that 9% by weight, only 3% by weight is currently recycled. Therefore, there remains an unmet need to achieve the automotive industry's plastic recycling targets. This invention focuses particularly on the mechanical recycling of waste streams, as opposed to "energy recovery" which involves incinerating polyolefins for energy production. However, due to cost, poor mechanical properties, and poor processing performance, waste streams containing cross-linked polyolefins are often used for energy recovery (e.g., incineration in district heating plants or for heat generation in the cement industry) and rarely recycled for new products.
[0005] A major trend in the polyolefin sector is the use of recycled materials from a variety of different sources. Durable goods streams, such as waste electrical equipment (WEE) or end-of-life vehicles (ELV), contain a variety of different plastics. These materials can be processed to recycle acrylonitrile-butadiene-styrene (ABS), high-impact polystyrene (HIPS), polypropylene (PP), and polyethylene (PE) plastics. Separation can be performed using density separation in water, followed by further separation based on fluorescence, near-infrared absorption, or Raman fluorescence. However, it is often difficult to obtain pure recycled polypropylene or pure recycled polyethylene. Generally, a large amount of recycled polypropylene on the market is often a mixture of polypropylene (PP) and polyethylene (PE); this is especially true for post-consumer waste streams. It has been found that commercially available recycled materials from post-consumer waste sources often contain a mixture of PP and PE, with minor components reaching <50% by weight.
[0006] The higher the quality of recycled polyolefins, i.e., the higher the purity, the more expensive the material. In addition, recycled polyolefin materials are often cross-contaminated by non-polyolefin materials, such as polyethylene terephthalate, polyamide, and polystyrene, or by non-polymer materials such as wood, paper, glass, or aluminum.
[0007] Furthermore, materials rich in recycled polypropylene typically exhibit significantly inferior performance compared to virgin materials unless the amount of recycled polyolefin added to the final blend is extremely low. For example, such materials often perform poorly in terms of odor and taste, have limited stiffness and impact strength, and exhibit poor mechanical properties (such as brittleness), thus failing to meet customer requirements.
[0008] Waste Management 153 (2022) 41-51 describes the production of cast films and biaxially oriented polypropylene films formed from recycled materials. The performance of these films is significantly inferior to that of the virgin grades (see Figure 4), leading the authors to conclude that a substantial amount of virgin material needs to be added to these recycled materials to provide films with acceptable performance (see Section 3.2.2.2). It also states that non-polyolefin contamination significantly impairs film performance, thus explicitly indicating that the removal of inorganic residues such as talc and TiO2 is a promising approach to improve these films. Unfortunately, these inorganic residues are often present in recycled materials as fillers and are therefore difficult to remove during mechanical recycling. Therefore, providing a suitable recycled material that avoids these known drawbacks would significantly promote the application of recycled materials in PP-based films. Resources, Conservation & Recycling 200 (2024) 107299 studied the recycling of labels derived from PET bottles and concluded that such processes are not industrially feasible. Summary of the Invention
[0009] This invention is based on the observation that certain high-purity recycled materials can be used to manufacture cast films with an unexpectedly favorable balance of mechanical and optical properties, wherein the high-purity recycled materials break the generally understood trend of negative effects associated with higher amounts of inorganic residues.
[0010] Therefore, the present invention relates to a cast film comprising one or more layers, wherein at least one of the one or more layers is composed of a polymer composition (PC), wherein the polymer composition (PC) comprises:
[0011] a) 0.0% to 80.0% by weight of virgin propylene polymer (v-PP) relative to the total weight of the polymer composition (PC); and
[0012] b) A blend of polypropylene (PPP) in the range of 20.0% to 100.0% by weight relative to the total weight of the polymer composition (PC), wherein the blend of polypropylene (PPP) has a melt flow rate (MFR2) in the range of 3.5 g / 10 min to 10.0 g / 10 min as determined according to ISO 1133 at 230 °C and 2.16 kg, wherein the polymer portion of the blend of polypropylene (PPP) has:
[0013] i) Ethylene content (C2(total)) in the range of 0.0 wt% to 5.0 wt% as determined by CRYSTEX QC analysis;
[0014] ii) The content of crystal fraction (CF) in the range of 93.0% to 100.0% by weight as determined by CRYSTEX QC analysis;
[0015] iii) The content of soluble fraction (SF) in the range of 0.0 wt% to 7.0 wt%, as determined by CRYSTEX QC analysis; and
[0016] iv) Ethylene content (C2(CF)) of the crystal fraction in the range of 0.0 wt% to 5.0 wt%, as determined by CRYSTEX QC analysis.
[0017] definition
[0018] Post-consumer waste refers to items that have completed at least their first use cycle (or life cycle), i.e., items that have fulfilled their first purpose; while industrial waste refers to manufacturing waste that usually does not reach consumers.
[0019] The recycled stream may contain both articles for recycling and fragments of those articles, such as flakes. In the context of this invention, the contents of the recycled stream are referred to as pieces, whether they are whole articles, fragments of those articles, or flakes of those articles. In some embodiments, a piece may be a flake, while in other embodiments, a piece may be a larger article that can be converted into a flake at a later stage.
[0020] In the context of this invention, a mixed plastic recycling stream can be any stream suitable for recycling, containing polyolefins, and the stream does not necessarily contain only a single polyolefin product; this is, for example, the case for some post-industrial waste recycling streams, where production waste of a single polyolefin grade or articles containing a single polyolefin may be the only items present in the stream. Generally, post-consumer waste recycling streams containing polyolefins will be mixed plastic recycling streams, as are many post-industrial waste recycling streams containing polyolefins. The "polyolefin recycling stream" according to the invention can be a mixed plastic recycling stream, or it may have undergone a pre-sorting process, thereby enriching it with a specific type of polyolefin. Alternatively or additionally, due to optimized waste collection management, where only certain types of waste are collected into a given recycling stream, the polyolefin recycling stream can have a high purity of one type of polyolefin.
[0021] As used herein, the term "product morphology" refers to the shape and form of products present in a polyolefin recycled stream. These products can be in particular in the form of films, packages, and bags, which can be considered flexible products; and they can also be in the form of molded products such as food containers, skincare containers, and plastic bottles, which can be considered rigid products. Commercial optical sorting machines such as Tomra Autosort, RTT Steinert Unisort, and Redwave Pellenc can separate so-called rigid and flexible products by utilizing their aerodynamic properties (i.e., typically by applying airflow to the stream, those that are rigid products will fall in an arc different from that of flexible products), thereby transforming a stream containing these products into so-called rigid and flexible streams.
[0022] Furthermore, those skilled in the art should recognize that the prior art sorting processes involved in automatic sorting machines of the type described below cannot achieve perfect sorting. This means that any statement such as “wherein the stream contains only a single color” or “wherein the stream contains only a single polyolefin type” should be interpreted broadly, where the stream described in this way essentially contains only the stated color or polyolefin type, but is not 100% pure due to technical limitations of the sorting steps.
[0023] Those skilled in the art will recognize that pH values greater than 14.0 and less than 0.0 are theoretically possible; however, they will also recognize that such pH values are extremely difficult to determine using conventional pH probes. Therefore, in the context of this invention, an aqueous solution with an effective pH greater than 14.0 is considered to have a pH of 14.0, and an aqueous solution with an effective pH less than 0.0 is considered to have a pH of 0.0.
[0024] In the context of this invention, the term "rinsing" is used to refer to the addition of a solvent (typically water) to remove foreign matter or residual liquid from the surface of a polyolefin. This process can be completed in a very short time, i.e., less than 5 minutes, typically less than 1 minute; in contrast, a "washing" step typically takes longer and requires agitation to remove attached foreign matter from the polyolefin surface, and may extract volatile organic compounds from the polyolefin.
[0025] When the term "comprising" is used in this specification and claims, it does not exclude other elements that are not explicitly stated but have primary or secondary functional importance. For the purposes of this invention, the term "consisting of" is considered a preferred embodiment of the term "comprising." If a group is defined below as including at least a certain number of elements, it should also be understood as disclosing a group preferably consisting only of those elements.
[0026] When referring to a singular noun and using the indefinite or definite article, such as "a," "an," or "the," it also includes the plural form of the noun unless otherwise explicitly stated. Detailed Implementation
[0027] This invention relates to a cast film comprising one or more layers, wherein at least one of the layers is composed of a polymer composition (PC), wherein the polymer composition (PC) comprises:
[0028] a) Virgin propylene polymer (v-PP) ranging from 0.0 wt% to 80.0 wt% relative to the total weight of the polymer composition (PC); and
[0029] b) A blend of polypropylene (PPC) in the range of 20.0% to 100.0% by weight relative to the total weight of the polymer composition (PC), wherein the blend of polypropylene (PPC) has a melt flow rate (MFR2) in the range of 3.5 g / 10 min to 10.0 g / 10 min as determined according to ISO 1133 at 230 °C and 2.16 kg, wherein the polymer portion of the blend of polypropylene (PPC) has:
[0030] i) Ethylene content (C2(total)) in the range of 0.0 wt% to 5.0 wt% as determined by CRYSTEX QC analysis;
[0031] ii) The content of crystal fraction (CF) in the range of 93.0% to 100.0% by weight as determined by CRYSTEX QC analysis;
[0032] iii) The content of soluble fraction (SF) in the range of 0.0 wt% to 7.0 wt%, as determined by CRYSTEX QC analysis; and
[0033] iv) Ethylene content (C2(CF)) of the crystal fraction in the range of 0.0 wt% to 5.0 wt%, as determined by CRYSTEX QC analysis.
[0034] Polymer composition (PC)
[0035] The polymer composition (PC) of the present invention comprises: a virgin propylene polymer (v-PP) ranging from 0.0 wt% to 80.0 wt% relative to the total weight of the polymer composition (PC); and a blended plastic polypropylene blend (B) ranging from 20.0 wt% to 100.0 wt% relative to the total weight of the polymer composition (PC).
[0036] Preferably, the polymer composition (PC) comprises the following components, more preferably it consists of the following components:
[0037] a) Virgin propylene polymer (v-PP) in the range of 0.0 wt% to 80.0 wt% relative to the total weight of the polymer composition (PC).
[0038] b) Mixed plastic polypropylene blends (B) ranging from 20.0% by weight to 100.0% by weight relative to the total weight of the polymer composition (PC);
[0039] c) Optionally, other polymeric components (P) ranging from 0.0% to 10.0% by weight relative to the total weight of the polymeric composition (PC); and
[0040] d) Optionally, additive (A) in the range of 0.0% to 5.0% by weight relative to the total weight of the polymer composition (PC).
[0041] Preferably, the polymer composition (PC) comprises the following components, more preferably it consists of the following components:
[0042] a) Virgin propylene polymer (v-PP) in the range of 0.0 wt% to 70.0 wt% relative to the total weight of the polymer composition (PC).
[0043] b) Mixed plastic polypropylene blends (B) ranging from 30.0% by weight to 100.0% by weight relative to the total weight of the polymer composition (PC).
[0044] c) Optionally, other polymeric components (P) ranging from 0.0% to 10.0% by weight relative to the total weight of the polymeric composition (PC); and
[0045] d) Optionally, additive (A) in the range of 0.0% to 5.0% by weight relative to the total weight of the polymer composition (PC).
[0046] In some embodiments, the polymer composition (PC) comprises, more preferably, the following components:
[0047] a) 0.0% to 80.0% by weight, more preferably 0.0% to 70.0% by weight, of virgin propylene polymer (v-PP) relative to the total weight of the polymer composition (PC).
[0048] b) A blend of mixed plastic polypropylene (B) in the range of 20.0% to 100.0% by weight, more preferably 30.0% to 100.0% by weight, relative to the total weight of the polymer composition (PC).
[0049] In some embodiments, the polymer composition (PC) comprises, more preferably, the following components:
[0050] a) 0.0% to 80.0% by weight, more preferably 0.0% to 70.0% by weight, of virgin propylene polymer (v-PP) relative to the total weight of the polymer composition (PC).
[0051] b) A mixed plastic polypropylene blend (B) in the range of 20.0% to 100.0% by weight, more preferably 30.0% to 100.0% by weight, relative to the total weight of the polymer composition (PC).
[0052] c) Other polymeric components (P) ranging from 0.0% to 10.0% by weight, more preferably from 0.1% to 5.0% by weight, relative to the total weight of the polymeric composition (PC).
[0053] In some embodiments, the polymer composition (PC) comprises, more preferably, the following components:
[0054] a) 0.0% to 80.0% by weight, more preferably 0.0% to 70.0% by weight, of virgin propylene polymer (v-PP) relative to the total weight of the polymer composition (PC).
[0055] b) A blend of mixed plastic polypropylene (B) in the range of 20.0% to 100.0% by weight, more preferably 30.0% to 100.0% by weight, relative to the total weight of the polymer composition (PC); and
[0056] c) Additives (A) ranging from 0.0% to 5.0% by weight relative to the total weight of the polymer composition (PC).
[0057] In some embodiments, the polymer composition (PC) comprises, more preferably, the following components:
[0058] a) 0.0% to 80.0% by weight, more preferably 0.0% to 70.0% by weight, of virgin propylene polymer (v-PP) relative to the total weight of the polymer composition (PC).
[0059] b) A mixed plastic polypropylene blend (B) in the range of 20.0% to 100.0% by weight, more preferably 30.0% to 100.0% by weight, relative to the total weight of the polymer composition (PC).
[0060] c) Other polymeric components (P) ranging from 0.0% to 10.0% by weight, more preferably from 0.1% to 5.0% by weight, relative to the total weight of the polymeric composition (PC); and
[0061] d) Additive (A) in the range of 0.0% to 5.0% by weight relative to the total weight of the polymer composition (PC).
[0062] Preferably, the total weight of the virgin propylene polymer (v-PP) and the blended plastic polypropylene blend (B) relative to the total weight of the polymer composition (PC) is at least 85% by weight, more preferably at least 90% by weight, and even more preferably at least 95% by weight.
[0063] More preferably, the total amount of virgin propylene polymer (v-PP) with the blended plastic polypropylene blend (B), optional other polymer components (P), and optional additives (A) relative to the total weight of the polymer composition (PC) is at least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight. Most preferably, the polymer composition (PC) consists of virgin propylene polymer (v-PP) and the blended plastic polypropylene blend (B), optional other polymer components (P), and optional additives (A).
[0064] More preferably, relative to the total weight of the polymer composition (PC), the polymer composition (PC) has an inorganic residue (ash residue) content in the range of 0.10 wt% to 7.5 wt%, more preferably 0.30 wt% to 5.0 wt%, and most preferably 0.50 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA).
[0065] In some embodiments, the polymer composition (PC) has an inorganic residue (ash residue) content in the range of 0.10 wt% to 7.5 wt%, more preferably 1.0 wt% to 5.0 wt%, and most preferably 2.0 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA), relative to the total weight of the polymer composition (PC).
[0066] Preferably, the polymer composition (PC) has a size of 80 × 10 × 4 mm prepared according to ISO 19069-2 according to ISO 178. 3 Flexural modulus measured on injection-molded specimens in the range of 1200 MPa to 1800 MPa.
[0067] Preferably, the polymer composition (PC) has a total luminous transmittance in the range of 70% to 100%, more preferably 75% to 100%, and most preferably 80% to 100% as determined by ASTM D1003 on a 50 µm cast film sample.
[0068] Preferably, the polymer composition (PC) has a clarity value in the range of 40% to 80%, more preferably 43% to 70%, and most preferably 45% to 60% as determined according to ASTM D1003 on a 50 µm cast film sample.
[0069] Preferably, the polymer composition (PC) has a haze value in the range of 20% to 80%, more preferably 30% to 70%, and most preferably 40% to 60% as determined according to ASTM D1003 on a 50 µm cast film sample.
[0070] Preferably, the polymer composition (PC) has a longitudinal (MD) 45° gloss value in the range of 20.0 to 35.0, more preferably 23.0 to 30.0, and most preferably 25.0 to 28.0, as determined by ASTM D2457 on a 50 µm cast film sample.
[0071] Preferably, the polymer composition (PC) has a transverse (TD) 45° gloss value in the range of 18.0 to 30.0, more preferably 20.0 to 28.0, and most preferably 22.0 to 25.0, as determined according to ASTM D2457 on a 50 µm cast film sample.
[0072] Preferably, the polymer composition (PC) has a tensile modulus in the range of 500 MPa to 1000 MPa, more preferably 600 MPa to 800 MPa, and most preferably 620 MPa to 700 MPa, as measured in the longitudinal direction (MD) on a 50 µm cast film specimen according to ISO 527-3.
[0073] Preferably, the polymer composition (PC) has a tensile modulus in the range of 450 MPa to 1000 MPa, more preferably 500 MPa to 800 MPa, and most preferably 520 MPa to 650 MPa, as measured in the transverse (TD) direction on a 50 µm cast film sample according to ISO 527-3.
[0074] Preferably, the polymer composition (PC) has a tensile stress at break in the range of 30 MPa to 70 MPa, more preferably 35 MPa to 60 MPa, and most preferably 40 MPa to 55 MPa, as measured in the longitudinal direction (MD) on a 50 µm cast film specimen according to ISO 527-3.
[0075] Preferably, the polymer composition (PC) has a tensile stress at break in the range of 12 MPa to 50 MPa, more preferably 20 MPa to 40 MPa, and most preferably 25 MPa to 35 MPa, as measured in the transverse (TD) direction on a 50 µm cast film specimen according to ISO 527-3.
[0076] Preferably, the polymer composition (PC) has a tensile strain at break in the range of 400% to 800%, more preferably 500% to 700%, and most preferably 580% to 650% as measured in the longitudinal direction (MD) on a 50 µm cast film specimen according to ISO 527-3.
[0077] Preferably, the polymer composition (PC) has a tensile strain at break in the range of 400% to 800%, more preferably 500% to 700%, and most preferably 550% to 630% as measured in the transverse (TD) direction on a 50 µm cast film specimen according to ISO 527-3.
[0078] Preferably, the polymer composition (PC) has a yield tensile stress in the range of 10 MPa to 30 MPa, more preferably 12 MPa to 25 MPa, and most preferably 13 MPa to 20 MPa, as measured in the longitudinal direction (MD) on a 50 µm cast film specimen according to ISO 527-3.
[0079] Preferably, the polymer composition (PC) has a yield tensile stress in the range of 10 MPa to 30 MPa, more preferably 12 MPa to 25 MPa, and most preferably 12 MPa to 20 MPa, as measured in the transverse (TD) direction on a 50 µm cast film specimen according to ISO 527-3.
[0080] Preferably, the polymer composition (PC) has a yield tensile strain in the range of 6.0% to 10.0%, more preferably 7.0% to 9.5%, and most preferably 7.5% to 9.0% as determined in the longitudinal direction (MD) on a 50 µm cast film specimen according to ISO 527-3.
[0081] Preferably, the polymer composition (PC) has a yield tensile strain in the range of 5.0% to 10.0%, more preferably 6.0% to 9.0%, and most preferably 6.5% to 8.0% as determined in the transverse (TD) direction on a 50 µm cast film specimen according to ISO 527-3.
[0082] The unexpected discovery of this invention is that, despite the presence of a high amount of inorganic residue, the recycled material-containing cast film of this invention still has mechanical properties comparable to the comparative cast film containing recycled material, and also has improved optical properties, which is particularly surprising.
[0083] Therefore, the preferred option is:
[0084] a) Relative to the total weight of the polymer composition (PC), the polymer composition (PC) has an inorganic residue (ash residue) content in the range of 0.10 wt% to 7.5 wt%, more preferably 1.0 wt% to 5.0 wt%, and most preferably 2.0 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA); and
[0085] b) The polymer composition (PC) has a haze value in the range of 20% to 80%, more preferably 30% to 70%, and most preferably 40% to 60% as determined on a 50 µm cast film specimen according to ASTM D1003.
[0086] Virgin propylene polymer (v-PP)
[0087] In its broadest sense, virgin propylene polymer (v-PP) can be any propylene polymer. In contrast to blended plastic polypropylene blends (B), the term "virgin" indicates that the virgin propylene polymer (v-PP) has not been used in other applications and has subsequently been recycled.
[0088] The virgin propylene polymer (v-PP) is preferably a propylene homopolymer (h-PP), a propylene random copolymer (r-PP), or a multiphase propylene copolymer (HECO).
[0089] In each of these embodiments, the melt flow rate (MFR2) measured according to ISO 1133 at 230°C and 2.16 kg is preferably in the range of 1.0 g / 10 min to 10.0 g / 10 min, more preferably 2.0 g / 10 min to 9.0 g / 10 min, and most preferably 3.0 g / 10 min to 8.0 g / 10 min.
[0090] Preferably, the virgin propylene polymer (v-PP) is a propylene homopolymer (h-PP) or a multiphase propylene copolymer (HECO).
[0091] Particularly preferred is that the virgin propylene polymer (v-PP) is a propylene homopolymer (h-PP) or a multiphase propylene copolymer (HECO), and even more preferably a multiphase propylene-ethylene copolymer (HECO).
[0092] Multiphase propylene-ethylene copolymers (HECOs) can be characterized using trichlorobenzene (TCB) as a solvent according to the CRYSTEX QC method. This method is described in the determination method section below. In some cases, this method yields more useful data (e.g., compared to methods based on xylene-based cold soluble fractions) because the crystalline fraction (CF) and soluble fraction (SF) more accurately correspond to the matrix and elastomer phases of the multiphase propylene-ethylene copolymer, respectively. Because the separation methods of xylene extraction and the CRYSTEX QC method differ, the properties of the XCS / XCI fraction on one hand are not entirely the same as those of the crystalline / soluble (CF / SF) fraction on the other hand. This means that the amounts and properties of the matrix phase (i.e., CF or XCI) and the elastomer phase (i.e., SF or XCS) may differ.
[0093] CRYSTEX QC analysis quantifies the properties of the soluble fraction (SF) and crystalline fraction (CF) of the polymeric portion of multiphase propylene-ethylene copolymer (HECO), thus disregarding any non-polymeric components such as talc and titanium dioxide.
[0094] Preferably, the multiphase propylene-ethylene copolymer (HECO) has a soluble fraction (SF) content in the range of 10.0% to 25.0% by weight, more preferably 11.0% to 20.0% by weight, and most preferably 12.0% to 18.0% by weight, as determined by CRYSTEX QC analysis.
[0095] Preferably, the multiphase propylene-ethylene copolymer (HECO) has a crystalline fraction (CF) content in the range of 75.0% to 90.0% by weight, more preferably 80.0% to 89.0% by weight, and most preferably 82.0% to 88.0% by weight, as determined by CRYSTEX QC analysis.
[0096] Preferably, the multiphase propylene-ethylene copolymer (HECO) has an ethylene content (C2(total)) in the range of 4.0 wt% to 10.0 wt%, more preferably 5.0 wt% to 9.0 wt%, and most preferably 6.0 wt% to 8.0 wt%, as determined by CRYSTEX QC analysis.
[0097] Preferably, the multiphase propylene-ethylene copolymer (HECO) has an ethylene content (C2(CF)) of crystalline fraction in the range of 1.0 wt% to 5.0 wt%, more preferably 1.5 wt% to 4.5 wt%, and most preferably 2.0 wt% to 4.0 wt%, as determined by CRYSTEX QC analysis.
[0098] Preferably, the multiphase propylene-ethylene copolymer (HECO) has an ethylene content (C2(SF)) in the soluble fraction within the range of 20.0% to 40.0% by weight, more preferably 25.0% to 37.0% by weight, and most preferably 30.0% to 35.0% by weight, as determined by CRYSTEX QC analysis.
[0099] Preferably, the multiphase propylene-ethylene copolymer (HECO) has an intrinsic viscosity (iV(total)) in the range of 1.20 dL / g to 3.00 dL / g, more preferably 1.50 dL / g to 2.70 dL / g, and most preferably 1.80 dL / g to 2.40 dL / g, as determined by CRYSTEX QC analysis.
[0100] Preferably, the multiphase propylene-ethylene copolymer (HECO) has an intrinsic viscosity (iV(CF)) of its crystalline fraction in the range of 1.20 dL / g to 3.00 dL / g, more preferably 1.50 dL / g to 2.70 dL / g, and most preferably 1.80 dL / g to 2.40 dL / g, as determined by CRYSTEX QC analysis.
[0101] Preferably, the multiphase propylene-ethylene copolymer (HECO) has an intrinsic viscosity (iV(SF)) of the soluble fraction in the range of 1.00 dL / g to 2.50 dL / g, more preferably 1.20 dL / g to 2.20 dL / g, and most preferably 1.40 dL / g to 2.00 dL / g, as determined by CRYSTEX QC analysis.
[0102] Blended plastic polypropylene blend (B)
[0103] In the context of this invention, the term "mixed plastic polypropylene blend" refers to a blend formed by the presence of more than one polymer grade. The blend does not necessarily contain polymers other than polypropylene; a blend comprising only multiple polypropylene fractions also constitutes a mixed plastic polypropylene blend according to the invention, which is at least partially derived from recycled materials. Such mixed plastic polypropylene blends are typically formed from multiple different virgin grades collected together during the recycling process; therefore, those skilled in the art can readily distinguish such mixed plastic polypropylene blends from virgin grades with well-defined modalities (e.g., unimodal, bimodal, etc.).
[0104] Preferably, the polypropylene-rich recycled material is obtained from recycled waste through plastic recycling processes known in the art. Such recycled materials are commercially available, for example from Corepla (Italian Consortium for the collection, recovery, recycling of packaging plastic wastes), Resource Plastics Corp. (Bampton, Ontario, Canada), Kruschitz GmbH, Plastics and Recycling (Austria), Vogt Plastik GmbH (Germany), Mtm Plastics GmbH (Germany), etc. Non-exhaustive examples of polypropylene-rich recycled materials include Purpolen® PP (Mtm Plastics GmbH), Axpoly® recycled polypropylene granules (Axion Ltd), and PolyPropylene Copolymer (BSP Compounds).
[0105] During recycling, any reasonable measures are typically taken to reduce / remove any components other than polyethylene and polypropylene, provided that such measures are recommended for the end application or use; however, other components are usually still present in small amounts.
[0106] Therefore, preferably, at least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight of the mixed plastic polypropylene blend (B) is derived from recycled materials.
[0107] Recycled materials are preferably derived from post-consumer waste, post-industrial waste, or a combination thereof, and more preferably from post-consumer waste.
[0108] Particularly preferably, at least 85% by weight of the recycled material originates from labels containing polypropylene. In particular, the recycled material is preferably derived from post-consumer waste, wherein at least 85% by weight originates from labels containing polypropylene.
[0109] Particularly preferred, the mixed plastic polypropylene blend (B) can be obtained by a mechanical polypropylene recycling process including the following steps performed in a given sequence, and more preferably by a mechanical polypropylene recycling process including the following steps performed in a given sequence:
[0110] a) Provide a precursor polypropylene recycled stream (A) based on the total weight of the precursor polypropylene recycled stream (A), which contains at least 85% by weight of polypropylene-containing labels.
[0111] b) Optionally, the precursor polypropylene recovery stream (A) is sorted by polymer type, thereby removing any contents containing polymers other than polypropylene, resulting in a purified polypropylene recovery stream (B).
[0112] c) Wash the purified polypropylene recycled stream (B) in one or more washing steps, or wash the precursor polypropylene recycled stream (A) in the absence of step b), thereby obtaining a washed polypropylene stream (C).
[0113] d) Optionally, the washed polypropylene stream (C) is separated into heavy fraction and light fraction polypropylene recycled stream (D).
[0114] e) Melt extrusion of the light-grade polypropylene recycled stream (D), or, in the absence of step d), of the washed polypropylene stream (C), preferably granulation, wherein an additive (Ad) is added in the molten state to form an extruded, preferably granulated, recycled polypropylene composition (E); and
[0115] f) Optionally, the recycled polypropylene composition (E) is aerated to remove volatile organic compounds, thereby producing an aerated extruded recycled polypropylene product (F1).
[0116] The order of steps f) and e) can be interchanged, such that the light-grade polypropylene recycled stream (D) is first aerated, or the washed polypropylene stream (C) is aerated in the absence of step d), to form aerated recycled polypropylene sheets (F2), which are then extruded, preferably with additives (Ad) added in the melt state, to form an extruded, preferably granulated and aerated recycled polypropylene product (F3).
[0117] The process is described in more detail in EP 23 200 103.2.
[0118] The blended plastic polypropylene blend (B) has a melt flow rate (MFR2) in the range of 3.5 g / 10 min to 10.0 g / 10 min, more preferably 4.0 g / 10 min to 8.0 g / 10 min, and most preferably 5.0 g / 10 min to 7.0 g / 10 min, as determined according to ISO 1133 at 230 °C and 2.16 kg.
[0119] Trichlorobenzene (TCB) can be used as a solvent to characterize blended polypropylene (B) plastics according to the CRYSTEX QC method. This method is described in the determination method section below. In some cases, this method produces more useful data (e.g., compared to methods based on xylene cold solubles) because the crystalline fraction (CF) and soluble fraction (SF) more accurately correspond to the matrix and elastomer phases of the multiphase propylene-ethylene copolymer, respectively. Because the separation methods of xylene extraction and the CRYSTEX QC method differ, the properties of the XCS / XCI fraction on one side are not entirely the same as those of the crystalline / soluble (CF / SF) fraction on the other side. This means that the amounts and properties of the matrix phase (i.e., CF or XCI) and the elastomer phase (i.e., SF or XCS) may differ.
[0120] CRYSTEX QC analysis quantifies the properties of the soluble fraction (SF) and crystalline fraction (CF) of the polymer portion of a blended plastic polypropylene blend (B), thus disregarding any non-polymer components such as talc and titanium dioxide.
[0121] The polymer portion of the mixed plastic polypropylene blend (B) has an ethylene content (C2(total)) in the range of 0.0 wt% to 5.0 wt%, more preferably 0.0 wt% to 4.0 wt%, and most preferably 0.0 wt% to 3.5 wt%, as determined by CRYSTEX QC analysis.
[0122] The polymer portion of the mixed plastic polypropylene blend (B) also has a crystalline fraction (CF) content in the range of 93.0% to 100.0% by weight, more preferably 93.5% to 99.0% by weight, and most preferably 94.0% to 99.0% by weight, as determined by CRYSTEX QC analysis.
[0123] The polymer portion of the mixed plastic polypropylene blend (B) also has a soluble fraction (SF) content in the range of 0.0 wt% to 7.0 wt%, more preferably 1.0 wt% to 6.5 wt%, and most preferably 1.0 wt% to 6.0 wt%, as determined by CRYSTEX QC analysis.
[0124] The polymer portion of the mixed plastic polypropylene blend (B) also has an ethylene content (C2(CF)) of the crystalline fraction in the range of 0.0 wt% to 5.0 wt%, more preferably 0.0 wt% to 4.0 wt%, and most preferably 0.0 wt% to 3.5 wt%, as determined by CRYSTEX QC analysis.
[0125] The polymer portion of the mixed plastic polypropylene blend (B) preferably has an intrinsic viscosity (iV(CF)) of the crystalline fraction within the range of 1.90 dL / g to 2.20 dL / g, more preferably 1.95 dL / g to 2.15 dL / g, and most preferably 2.00 dL / g to 2.10 dL / g, as determined by CRYSTEX QC analysis.
[0126] As described above, the blended plastic polypropylene blend (B) is at least partially derived from recycled materials. Preferably, at least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight of the blended plastic polypropylene blend (B) is derived from recycled materials.
[0127] If native polymers are available, these polymers are preferably masterbatch carrier polymers used to introduce additives during compounding.
[0128] The blended plastic polypropylene blend (B) according to embodiments of the present invention also has a unique light gray coloring, which is mainly due to the combination of trace inks that may not be 100% removed during the recycling process. The more effective the washing process, the less noticeable this gray coloring (i.e., the whiter the blended plastic polypropylene blend (B)). Other non-polypropylene components may also directly contribute to the ashing effect, or contribute to the ashing effect by forming degradation products that promote the ashing effect.
[0129] Therefore, the blended plastic polypropylene blend (B) preferably has the following CIELAB color space (L*a*b) as determined according to ISO 11664-4:
[0130] i) L* is 50.0 to 90.0, more preferably 50.0 to 85.0;
[0131] ii) a* is between -5.0 and 0.0; and
[0132] iii) b* is between 0.0 and 25.0.
[0133] This type of CIELAB color space is typical for particularly pure recycled materials (i.e., whiter than regular recycled materials, but not as white as white virgin polymer grades).
[0134] Although it is possible to obtain native grades with colors within the CIELAB color space, this is usually achieved by adding a small amount of black pigment, such as carbon black, to a white polymer grade, meaning that the native grade will contain only white and black pigments.
[0135] In the mixed plastic polypropylene blend (B) of the present invention, the gray coloring is not due to the addition of black pigment, but to trace amounts of various colored inks.
[0136] While typical black pigments contain carbon (i.e., carbon black), and white pigments contain, for example, titanium (in the form of titanium dioxide), mixed inks will contain a variety of different elements that can be detected by X-ray fluorescence spectroscopy (XRF). These same diverse elements are not detectable in otherwise equivalent gray primary materials.
[0137] Therefore, XRF analysis revealed the following elements indicating that the blended plastic polypropylene blend (B) has a recycling source. For the following XRF element contents, the use of the term "preferred" does not imply that higher amounts of the relevant element are ideal, but rather that "more preferred" and "most preferred" embodiments more precisely define the recycling source of the blended plastic polypropylene blend (B).
[0138] Therefore, preferably, the mixed plastic polypropylene blend (B) has an aluminum (Al) content of at least 60 ppm, more preferably at least 90 ppm, and most preferably at least 120 ppm as determined by X-ray fluorescence spectroscopy (XRF).
[0139] More preferably, the mixed plastic polypropylene blend (B) has an iron (Fe) content of at least 30 ppm, more preferably at least 50 ppm, and most preferably at least 80 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0140] More preferably, the mixed plastic polypropylene blend (B) has a sodium (Na) content of at least 30 ppm, more preferably at least 50 ppm, and most preferably at least 80 ppm, as determined by X-ray fluorescence spectrometry (XRF).
[0141] More preferably, the mixed plastic polypropylene blend (B) has a sulfur (S) content of at least 5 ppm, more preferably at least 15 ppm, and most preferably at least 30 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0142] More preferably, the mixed plastic polypropylene blend (B) has a zinc (Zn) content of at least 25 ppm, more preferably at least 40 ppm, and most preferably at least 45 ppm as determined by X-ray fluorescence spectroscopy (XRF).
[0143] Particularly preferably, the mixed plastic polypropylene blend (B) has at least three, more preferably all, of the following properties:
[0144] a) An iron (Fe) content of at least 30 ppm as determined by X-ray fluorescence spectrometry (XRF);
[0145] b) A sodium (Na) content of at least 30 ppm as determined by X-ray fluorescence spectrometry (XRF); and
[0146] c) Sulfur (S) content of at least 5 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0147] d) A zinc (Zn) content of at least 25 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0148] Such combinations of Fe, Na, S, and / or Zn were not observed in the original grades. Therefore, the presence of these elements indicates the recycled nature of the blended plastic polypropylene (B), especially when combined with the aforementioned CIELAB color space.
[0149] Particularly preferably, the sum of the iron (Fe), sodium (Na), sulfur (S) and zinc (Zn) contents, as determined by X-ray fluorescence spectrometry (XRF), is at least 100 ppm, more preferably at least 200 ppm, and most preferably at least 400 ppm.
[0150] Similarly, the presence of such a high Al content is a clear indication of the recycled nature of the blended plastic polypropylene (B), especially for recycled materials derived from the label.
[0151] More preferably, the mixed plastic polypropylene blend (B) has a bromine (Br) content of at least 0.5 ppm, more preferably at least 1.0 ppm, and most preferably at least 2.0 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0152] More preferably, the mixed plastic polypropylene blend (B) has a potassium (K) content of at least 1 ppm, more preferably at least 10 ppm, and most preferably at least 20 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0153] More preferably, the mixed plastic polypropylene blend (B) has a strontium (Sr) content of at least 1 ppm, more preferably at least 5 ppm, and most preferably at least 10 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0154] More preferably, the mixed plastic polypropylene blend (B) has a calcium (Ca) content of at least 200 ppm, more preferably at least 500 ppm, and most preferably at least 800 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0155] More preferably, the mixed plastic polypropylene blend (B) has a chlorine (Cl) content of at least 25 ppm, more preferably at least 35 ppm, and most preferably at least 40 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0156] More preferably, the mixed plastic polypropylene blend (B) has a titanium (Ti) content of at least 600 ppm, more preferably at least 800 ppm, and most preferably at least 1000 ppm as determined by X-ray fluorescence spectroscopy (XRF).
[0157] More preferably, the mixed plastic polypropylene blend (B) has a magnesium (Mg) content of at least 50 ppm, more preferably at least 80 ppm, and most preferably at least 90 ppm as determined by X-ray fluorescence spectrometry (XRF).
[0158] More preferably, the mixed plastic polypropylene blend (B) has a silicon (Si) content of at least 50 ppm, more preferably at least 100 ppm, and most preferably at least 120 ppm as determined by X-ray fluorescence spectroscopy (XRF).
[0159] Another indicator of the recycled properties of polypropylene blends (B) can be obtained by measuring phosphorus (P) content.
[0160] Almost 100% of the phosphorus present in polymer grades can be attributed to phosphorus-based stabilizers, such as antioxidants. In almost all commercially available grades, the amount of such additives in the virgin grade is very consistent, corresponding to an amount sufficient to stabilize the polymer grade for the expected number of compounding steps (since oxidation is typically most likely to occur during these high-temperature compounding steps), without using excessive stabilizers that would result in unnecessary costs. When consumer products are recycled, the stabilizers are largely depleted (i.e., the stabilizers have been oxidized and can no longer be used as antioxidants), and additional phosphorus-based stabilizers are required to stabilize the recycled grade. This means that in the recycled grade, the phosphorus present will be: a) at the typical level of the virgin grade, but primarily in an oxidized state; or b) at a level significantly higher than the typical level of the virgin grade.
[0161] Total phosphorus content can be analyzed by X-ray fluorescence spectrometry (XRF), while the ratio of unoxidized stabilizer (tris(2,4-di-tert-butylphenyl) phosphite) to oxidized stabilizer (tris(2,4-di-tert-butylphenyl) phosphate) can be assessed by HPLC analysis.
[0162] Therefore, preferably, the tris(2,4-di-tert-butylphenyl) phosphate content, expressed as a percentage of the total content of tris(2,4-di-tert-butylphenyl) phosphate and tris(2,4-di-tert-butylphenyl) phosphate as determined by HPLC analysis, is in the range of 60% to 100%, and the total phosphorus content, determined by X-ray fluorescence spectrometry (XRF), is in the range of 15 ppm to 60 ppm.
[0163] This will be consistent with the grade of recycled material without further additives.
[0164] Alternatively, preferably, the total phosphorus content, as determined by X-ray fluorescence spectrometry (XRF), is greater than 60 ppm.
[0165] This will be consistent with recycled feed grades that have had additional phosphorus sources added.
[0166] More preferably, relative to the total weight of the mixed plastic polypropylene blend (B), the mixed plastic polypropylene blend (B) has an inorganic residue (ash residue) content in the range of 0.10 wt% to 7.5 wt%, more preferably 1.0 wt% to 5.0 wt%, and most preferably 2.0 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA).
[0167] The mixed plastic polypropylene blend (B) preferably has a total volume of organic compounds (TVOC) in the range of 0 µg / g to 25 µg / g, more preferably 0 µg / g to 18 µg / g, and most preferably 0 µg / g to 15 µg / g, as determined according to the measurement method given in the determination method.
[0168] The mixed plastic polypropylene blend (B) preferably has a total composite defect index value in the range of 4,000 to 35,000, more preferably 8,000 to 30,000, and most preferably 10,000 to 25,000, as determined by the method given in the determination method.
[0169] The mixed plastic polypropylene blend (B) preferably has a number of combined defects in the range of 20,000 to 200,000, more preferably 30,000 to 180,000, and most preferably 40,000 to 150,000, as determined by the method given in the determination method.
[0170] The blended plastic polypropylene blend (B) preferably has a density of at least 1.10 g / cm³ in the range of 0.10 vol% to 0.60 vol%, more preferably 0.20 vol% to 0.55 vol%, and most preferably 0.30 vol% to 0.50 vol%, as determined by X-ray computed tomography. 3 The content of particulate pollutants.
[0171] The blended plastic polypropylene blend (B) preferably has a density of at least 1.10 g / cm³ in the range of 0.05 vol% to 0.20 vol%, more preferably 0.07 vol% to 0.18 vol%, and most preferably 0.09 vol% to 0.15 vol%, as determined by X-ray computed tomography. 3 And the content of particulate pollutants with a size greater than 50 µm.
[0172] The mixed plastic polypropylene blend (B) preferably has a density of 1.10 g / cm³ in the range of 0.10 vol% to 0.35 vol%, more preferably 0.12 vol% to 0.28 vol%, and most preferably 0.15 vol% to 0.20 vol%, as determined by X-ray computed tomography. 3 Up to 1.53 g / cm 3 The content of particulate pollutants.
[0173] The blended plastic polypropylene blend (B) preferably has a density of 1.10 g / cm³ in the range of 0.01 vol% to 0.12 vol%, more preferably 0.02 vol% to 0.09 vol%, and most preferably 0.03 vol% to 0.06 vol%, as determined by X-ray computed tomography. 3 Up to 1.53 g / cm 3 And the content of particulate pollutants with a size greater than 50 µm.
[0174] Other polymer components (P)
[0175] In addition to virgin propylene polymers and blended plastic polypropylene blends, the polymer composition (PC) may also include small amounts of other polymer components (P).
[0176] The properties of these other polymer components (P) are not limited. Suitable other polymer components may include other polyethylene and / or polypropylene.
[0177] As described below, any masterbatch carrier polymer used to introduce additives is included in the total content of one or more additives (A).
[0178] Preferably, any other polymer component (P) is present in small amounts relative to the total weight of the polymer composition, for example, in an amount of 10.0% by weight or less, thereby ensuring that the majority of the polymer content in the polymer composition (PC) is derived from the blended plastic polypropylene blend (B) and / or virgin propylene polymer (v-PP).
[0179] One or more additives (A)
[0180] Another optional component of the polymer composition (PC) is one or more additives (A).
[0181] If present, one or more additives (A) are provided in an amount ranging from 0.0% to 5.0% by weight relative to the total weight of the polymer composition (PC).
[0182] Selecting suitable additives for polymer compositions (PC) is common knowledge to those skilled in the art.
[0183] For example, one or more additives (A) may be selected from the group consisting of antioxidants, stabilizers, fillers, nucleating agents and antistatic agents.
[0184] These additives are generally commercially available and are described, for example, in Hans Zweifel's "Plastic Additives Handbook", 5th edition, 2001, pp. 871-873.
[0185] It should be understood that the amount of additive (A) given relative to the total weight of the polymer composition (PC) includes any carrier polymer used to introduce the additive into the polymer composition (PC), i.e., a masterbatch carrier polymer. An example of such a carrier polymer is a polypropylene homopolymer in powder form.
[0186] Cast film
[0187] The cast film according to the invention comprises one or more layers, wherein at least one of the one or more layers is composed of a polymer composition (PC).
[0188] In one embodiment, the cast film is a single-layer film, wherein the single-layer film is composed of a polymer composition (PC).
[0189] In an alternative embodiment, the cast film is a multilayer film, particularly a three-layer film.
[0190] If the cast film is a three-layer film, the core layer is preferably composed of a polymer composition (PC).
[0191] If the cast film is a multilayer film, at least one layer must consist of a polymer composition (PC). The remaining layers may also include the polymer composition (PC) of the present invention, or may include polymer compositions different from the polymer composition (PC) of the present invention.
[0192] The cast film preferably has a thickness in the range of 10 µm to 200 µm, more preferably 20 µm to 100 µm, and most preferably 30 µm to 80 µm.
[0193] The cast film preferably has a total light transmittance in the range of 70% to 100%, more preferably 75% to 100%, and most preferably 80% to 100% as determined by ASTM D1003.
[0194] The cast film preferably has a clarity value in the range of 40% to 80%, more preferably 43% to 70%, and most preferably 45% to 60% as determined according to ASTM D1003.
[0195] The cast film preferably has a haze value in the range of 20% to 80%, more preferably 30% to 70%, and most preferably 40% to 60% as determined according to ASTM D1003.
[0196] The cast film preferably has a longitudinal (MD) 45° gloss value in the range of 20.0 to 35.0, more preferably 23.0 to 30.0, and most preferably 25.0 to 28.0 as determined by ASTM D2457.
[0197] The cast film preferably has a transverse (TD) 45° gloss value in the range of 18.0 to 30.0, more preferably 20.0 to 28.0, and most preferably 22.0 to 25.0 as determined according to ASTM D2457.
[0198] The cast film preferably has a tensile modulus in the range of 500 MPa to 1000 MPa, more preferably 600 MPa to 800 MPa, and most preferably 620 MPa to 700 MPa, as measured in the longitudinal direction (MD) according to ISO 527-3.
[0199] The cast film preferably has a tensile modulus in the range of 450 MPa to 1000 MPa, more preferably 500 MPa to 800 MPa, and most preferably 520 MPa to 650 MPa, as measured in the transverse (TD) direction according to ISO 527-3.
[0200] The cast film preferably has a tensile stress at break in the range of 30 MPa to 70 MPa, more preferably 35 MPa to 60 MPa, and most preferably 40 MPa to 55 MPa, as measured in the longitudinal direction (MD) according to ISO 527-3.
[0201] The cast film preferably has a tensile stress at break in the range of 12 MPa to 50 MPa, more preferably 20 MPa to 40 MPa, and most preferably 25 MPa to 35 MPa, as measured in the transverse (TD) direction according to ISO 527-3.
[0202] The cast film preferably has a tensile strain at break in the range of 400% to 800%, more preferably 500% to 700%, and most preferably 580% to 650% as measured in the longitudinal direction (MD) according to ISO 527-3.
[0203] The cast film preferably has a tensile strain at break in the range of 400% to 800%, more preferably 500% to 700%, and most preferably 550% to 630% as measured in the transverse (TD) direction according to ISO 527-3.
[0204] The cast film preferably has a yield tensile stress in the range of 10 MPa to 30 MPa, more preferably 12 MPa to 25 MPa, and most preferably 13 MPa to 20 MPa, as measured in the longitudinal direction (MD) according to ISO 527-3.
[0205] The cast film preferably has a yield tensile stress in the transverse (TD) range of 10 MPa to 30 MPa, more preferably 12 MPa to 25 MPa, and most preferably 12 MPa to 20 MPa, as determined according to ISO 527-3.
[0206] The cast film preferably has a yield tensile strain in the range of 6.0% to 10.0%, more preferably 7.0% to 9.5%, and most preferably 7.5% to 9.0% as determined in the longitudinal direction (MD) according to ISO 527-3.
[0207] The cast film preferably has a yield tensile strain in the range of 5.0% to 10.0%, more preferably 6.0% to 9.0%, and most preferably 6.5% to 8.0% as determined in the transverse (TD) direction according to ISO 527-3.
[0208] The present invention unexpectedly discovered that, despite the presence of a high amount of inorganic residues, the recycled material-containing cast film of the present invention still possesses mechanical properties comparable to the comparative cast film containing recycled materials, and also has improved optical properties, which is particularly surprising.
[0209] Therefore, the preferred option is:
[0210] a) The polymer composition (PC) has an inorganic residue (ash residue) content in the range of 1.0 wt% to 5.0 wt%, most preferably 2.0 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA), relative to the total weight of the polymer composition (PC);
[0211] b) The cast film has a thickness ranging from 20 µm to 100 µm, most preferably from 30 µm to 80 µm; and
[0212] c) The cast film has a haze value in the range of 20% to 80%, more preferably 30% to 70%, and most preferably 40% to 60% as determined by ASTM D1003.
[0213] Example
[0214] 1. Measurement Method
[0215] Unless otherwise defined, the following terms and measurement methods apply to the above general description of the invention, including the claims, and the following embodiments.
[0216] CRYSTEX QC Analysis
[0217] Methods for crystallization and soluble fractionation
[0218] Following ISO 16152-2022-Method 2, the crystallization fraction (CF) and soluble fraction (SF) of PCR polypropylene resin, as well as the ethylene content and intrinsic viscosity of each fraction, were analyzed using a CRYSTEX instrument from Polymer Char (Valencia, Spain). Detailed information on this technique and method can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020) Rapid characterization of high-impact ethylene–propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25:8, 581-596).
[0219] The crystalline and amorphous fractions were separated by a temperature cycle of dissolution at 160 °C, crystallization at 40 °C, and redissolution in 1,2,4-trichlorobenzene at 160 °C. Quantification of SF and CF, as well as determination of ethylene content (C2), were achieved using an integrated infrared detector (IR4), and intrinsic viscosity (IV) was determined using an online dual-capillary viscometer.
[0220] The IR4 detector is a multi-wavelength detector that measures IR absorbance at two different wavelengths, which relate to the CH3 stretching vibration (centered at approximately 2960 cm⁻¹). -1 ) and CH stretching vibration (2700 cm) -1 Up to 3000cm -1The IR4 detector was used to determine the concentration and ethylene content in ethylene-propylene copolymers. An IR4 detector was calibrated using a series of eight EP copolymers with known ethylene contents ranging from 2 wt% to 69 wt% (determined by 13C-NMR), with each EP copolymer used at different concentrations ranging from 2 mg / ml to 13 mg / ml. To account for both concentration and ethylene content for a variety of polymer concentrations expected during Crystex analysis, the following calibration equation was used:
[0221] Conc = a + b*Abs(CH) + c*(Abs(CH)) 2 + d*Abs(CH3) + e*(Abs(CH3) 2 + f*Abs(CH)*Abs(CH3) (Equation 1)
[0222] CH3 / 1000C = a + b*Abs(CH) + c*Abs(CH3) + d*(Abs(CH3) / Abs(CH)) + e*(Abs(CH3) / Abs(CH)) 2 (Equation 2)
[0223] The constants a to e in equation 1 and the constants a to f in equation 2 are determined using least squares regression analysis.
[0224] Use the following relationship to convert CH3 / 1000C to ethylene content in weight percent:
[0225] Weight % (ethylene in EP copolymer) = 100 - CH3 / 1000TC * 0.3 (Equation 3)
[0226] The intrinsic viscosity (IV) of PCR polypropylene resin and its soluble and crystalline fractions was determined using an online dual-capillary viscometer and correlated with the corresponding IV determined according to ISO 1628-3 in decahydronaphthalene by a standard method. Calibration was performed using various EP / PP copolymers with IV values ranging from 2 dL / g to 4 dL / g. The determined calibration curves were linear.
[0227] IV (dL / g) = a*Vsp / c (Equation 4)
[0228] Weigh the sample to be analyzed at a concentration of 10 mg / ml to 20 mg / ml. To avoid injecting possible gels and / or polymers (e.g., PET and PA) that are insoluble in TCB at 160°C, place the weighed sample into a stainless steel mesh of MW 0.077 / D 0.05 mm.
[0229] After automatically filling vials with 1,2,4-TCB containing 250 mg / L of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample is dissolved at 160 °C until completely dissolved, typically for 60 min with continuous stirring at 400 rpm. To prevent sample degradation, the polymer solution is covered with a nitrogen atmosphere during dissolution.
[0230] A specified volume of sample solution is injected into a column packed with an inert support, where crystallization of the sample and separation of the soluble fraction from the crystalline fraction occur. This process is repeated twice. During the first injection, the entire sample is measured at high temperature to determine the IV [dL / g] and C2 [wt%] of the PP composition. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) are measured using a crystallization cycle (wt% SF, wt% CF, wt% C2, wt% C2(SF), wt% C2(CF), IV(SF), IV(CF)), where wt% CF is calculated as follows:
[0231] % CF by weight = 100 - % SF by weight (Equation 5)
[0232] melt flow rate
[0233] Melt flow rate (MFR) was determined according to ISO 1133 and expressed in g / 10 min. MFR indicates the flowability of a polymer and thus its processability. A higher melt flow rate generally indicates a lower polymer viscosity. The MFR2 of polypropylene was determined at a temperature of 230°C and a load of 2.16 kg.
[0234] Xylene cold solubles (XCS)
[0235] The xylene-soluble fraction (XS) defined and described in this invention was determined according to ISO 16152 as follows: 2.0 g of polymer was dissolved in 250 ml of p-xylene at 135°C with stirring. After 30 minutes, the solution was cooled at ambient temperature for 15 minutes, and then allowed to stand at 25 ± 0.5°C for 30 minutes. The solution was filtered through filter paper into two 100 ml flasks. The solution in the first 100 ml container was evaporated under a nitrogen stream, and the residue was dried under vacuum at 90°C until constant weight was achieved. The xylene-soluble fraction (percentage) was then determined as follows:
[0236] XS%=(100*m*V0) / (m0*v); m0=initial polymer amount (g); m=residue weight (g); V0=initial volume (ml); v=volume of the sample analyzed (ml).
[0237] Flexural modulus was determined according to ISO 178 Method A (three-point bending test) on an 80 mm × 10 mm × 4 mm specimen. The test speed was 2 mm / min and the span length was 16 times the thickness, as per the standard. The test temperature was 23 ± 2 °C. Regardless of the melt flow rate of the material, injection molding was performed at a melt temperature of 230 °C according to ISO 19069-2.
[0238] Longitudinal and transverse tensile properties were determined at 23°C on a 50 µm thick monolayer cast film prepared as described below, according to ISO 527-1 / -3. In addition, the tensile modulus (secant modulus between 0.05% and 0.25% elongation) was also determined. The tensile modulus was determined at a crosshead speed of 1 mm / min, and then the test speed was increased to 200 mm / min until the film fractured.
[0239] X-ray fluorescence (XRF)
[0240] The instrument used for XRF measurements was a Malvern Panalytical wavelength-dispersive Zetium (2.4 kW). The instrument was calibrated according to the table below using Malvern Panalytical's Adpol, RoHS, and Toxel standards, as well as a set of custom calibration standards (hereinafter referred to as "Custom") also from Malvern Panalytical:
[0241]
[0242] A plate with a diameter of 40 mm and a thickness of 2 mm was analyzed under vacuum.
[0243] This method is used to determine the quantitative content of Na, Mg, Al, Si, P, S, Ca, Ti, Zn, Cu, Br, Cl, K, Sr and Fe in a given polyolefin matrix within the specified range of these standards.
[0244] The following standards were used to evaluate the content of each precise element (LOD = limit of detection):
[0245]
[0246] Elements not covered by the calibration standards or whose concentrations are outside the calibrated standard range are then analyzed in a semi-quantitative mode (using Omnian software from Malvern Panalytical). For elements not covered by the calibration standards, if the corresponding peak is not visible and therefore cannot be analyzed using Omnian software, no value is reported.
[0247] The CH content required for semi-quantitative assessment using Omnian is estimated by the software itself.
[0248] In the context of this invention, the presence of multiple elements (at least certainly not in combination) that are not typically encountered in virgin polymer grades indicates that a particular polypropylene grade is at least partially derived from recycled materials.
[0249] The table below lists typical data for several native and several recycled grades (i.e., r-PP), which indicate the presence of certain elements that indicate the recycling source:
[0250]
[0251] *Measured before the addition of the additive (i.e., before the addition of another fresh stabilizer, while all other r-PP values were measured after the addition of the additive).
[0252] **- Observed only in some samples, not in all samples.
[0253] HPLC analysis
[0254] Following extraction with ethyl acetate, the content of antioxidants (such as compounds from Irganox® 1010 and Irgafos® 168, namely pentaerythritol tetrakis(3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate) and tris(2,4-di-tert-butylphenyl) phosphite, and their oxidized variants) was determined by high-performance liquid chromatography (HPLC). First, approximately 10 g of the sample was cryogenically ground using liquid nitrogen. Then, 0.5 g of the ground sample was extracted using ethyl acetate as a solvent. Extraction was performed at 95°C for 90 min with continuous stirring. After the mixture was cooled back to room temperature, it was filtered and analyzed by HPLC to quantify the antioxidants. The HPLC system was equipped with a C18 column for separation and a diode array detector (DAD) for detection.
[0255] Almost 100% of the phosphorus present in polymer grades can be attributed to phosphorus-based stabilizers, such as antioxidants. In almost all commercially available grades, the amount of such additives in the virgin grades is very consistent, corresponding to an amount sufficient to stabilize the polymer grade for the expected number of compounding steps (since oxidation is typically most likely to occur during these high-temperature compounding steps), without using excessive stabilizers that would result in unnecessary costs. When consumer products are recycled, the stabilizers are largely depleted (i.e., the stabilizers have been oxidized and can no longer be used as antioxidants), and additional phosphorus-based stabilizers are required to stabilize the recycled grades. This means that in the recycled materials, the phosphorus present will be: a) at the typical level of the virgin grades, but primarily in an oxidized state; or b) at a level significantly higher than the typical level of the virgin grades (see Virgin Grades 1 to 3 in the previous table).
[0256] The table below discloses typical values for recycled materials corresponding to scenario a) (i.e., no additives have been added during mechanical recycling) and scenario b) (i.e., additives have been added during mechanical recycling).
[0257]
[0258] #1 to #4 have typical phosphorus contents as determined by XRF, but a high percentage of Irgafos are present in oxidized form, while #5 to #10 have higher phosphorus contents as determined by XRF than those observed in virgin polypropylene grades.
[0259] Other tests are presented graphically in Figure 1, showing the exact same trend (Note: the original grade will be located somewhere in the lower left of Figure 1, with a lower total P content of 28 ppm to 52 ppm and a lower percentage of oxidized Irgafos 168).
[0260] TVOC – Total Volatile Organic Compounds
[0261] Total volatile organic compounds (TVOC) were determined by HS-GC-FID / MS.
[0262] TVOC was measured directly on the granular sample (i.e., without any grinding or other size reduction).
[0263] Headspace settings: 100°C, 2 hours, 1 gram sample.
[0264] Specific components are quantified using the signal from the FID chromatogram and external standards for those components. TVOC is semi-quantitatively determined using toluene equivalents by using all peaks in the sample's FID chromatogram.
[0265] The analysis was performed twice.
[0266] The amounts of iPP, polystyrene, polyethylene (and ethylene-containing copolymers), polyethylene terephthalate, and polyamide-6.
[0267] Sample preparation:
[0268] All calibration samples and samples to be analyzed were prepared on fused plates in a similar manner.
[0269] Approximately 2 to 3 g of the analyte compound was melted at 190 °C. Subsequently, a pressure of 60 to 80 bar was applied for 20 seconds in a hydraulic hot press. The sample was then cooled to room temperature in a cold press under the same pressure for 40 seconds to control the morphology of the compound. The plate thickness was controlled using a metal calibration frame plate measuring 2.5 cm × 2.5 cm with a thickness of 100 µm to 200 µm (depending on the MFR of the sample); two plates were prepared simultaneously in parallel under the same conditions. The thickness of each plate was measured before any FTIR measurements; all plates had a thickness of 100 µm to 200 µm.
[0270] To control the surface of the boards and avoid any interference during measurement, all boards were pressed between two sheets of double-sided silicone release paper.
[0271] For powder samples or heterogeneous compounds, the pressing process is repeated three times to press and cut the sample under the same conditions as described above to improve homogeneity.
[0272] Spectrometer:
[0273] A standard transmission FTIR spectrometer, such as the Bruker Vertex 70 FTIR spectrometer, was used with the following settings:
[0274] The spectral range is 4000 cm⁻¹. -1 Up to 400 cm -1 ,
[0275] The aperture is 6 mm.
[0276] o spectral resolution 2 cm -1 ,
[0277] Background scan 16 times, spectral scan 16 times.
[0278] The zero-fill factor of the interferogram is 32.
[0279] oNorton-Beer strong apodisation (also known as toe cutting).
[0280] The spectra were recorded and analyzed using Bruker Opus software.
[0281] Calibration sample:
[0282] Since FTIR is a secondary method, several calibration standards are mixed to cover the target analytical range, typically as follows:
[0283] o For PA, it is 0.2% to 2.5% by weight;
[0284] o For PS, it is 0.1% to 5% by weight;
[0285] For PET, it is 0.2% to 2.5% by weight;
[0286] For PVC, the percentage is 0.1% to 4% by weight.
[0287] The following commercially available materials were used in the compound: Borealis HC600TF for iPP, Borealis FB3450 for HDPE, and for the target polymers, RAMAPET N1S (Indorama Polymer) for PET, Ultramid® B36LN (BASF) for polyamide 6, Styrolution PS 486N (Ineos) for high-impact polystyrene (HIPS), and Inovyn PVC 263B (in powder form) for PVC.
[0288] All blends were prepared on a small scale in a Haake kneader at temperatures below 265°C for less than 10 minutes to avoid degradation.
[0289] Add additional antioxidants such as Irgafos 168 (3000 ppm) to minimize degradation.
[0290] calibration:
[0291] All components are calibrated using the same FTIR principle: the intensity of a specific FTIR band divided by the plate thickness, and the result obtained on the same plate. 1 H or 13 The component amounts determined by C solution NMR are correlated.
[0292] Each specific FTIR absorption band was chosen because its intensity increases with increasing component concentration and because it is separated from the remaining peaks, regardless of the composition of the calibration standard and the actual sample.
[0293] This method is described in Signoret et al.'s publication "Alterations of plastic spectra in MIR and the potential impacts on identification towards recycling", Resources, Conservation and Recycling journal, 2020, Vol. 161, Article 104980.
[0294] The wavelengths of each calibration band are:
[0295] For PA, the value is 3300 cm. -1 ,
[0296] o for PS, is 1601 cm -1 ,
[0297] For PET, it is 1410 cm. -1 ,
[0298] For PVC, the value is 615 cm. -1 ,
[0299] o for iPP is 1167 cm -1 .
[0300] For each polymer component i, a linear calibration is constructed (based on the Beer-Lambert law). Typical linear relationships used for this type of calibration are shown below:
[0301]
[0302] Where xi is the fractional component of polymer component i (in weight %).
[0303] Ei represents the absorbance intensity of a specific spectral band associated with polymer component i (in units of absorbance au, see above for values).
[0304] d is the thickness of the sample plate.
[0305] Ai and Bi are two correlation coefficients determined for each calibration curve.
[0306] For the rich C2 fraction, no specific independent bands were found, therefore the rich C2 fraction was estimated indirectly.
[0307]
[0308] The chalk and talc contents were estimated "semi-quantitatively." Therefore, this makes the C2-rich content "semi-quantitative."
[0309] For each calibration standard, use it whenever possible. 1 H or 13 C solution NMR was used as the primary method to determine the amount of each component (except PA). NMR measurements were performed on the exact same FTIR plate used to construct the FTIR calibration curves.
[0310] Amount of talc and chalk
[0311] Talc and chalk content were measured by thermogravimetric analysis (TGA); experiments were conducted using a Perkin Elmer TGA 8000. Approximately 15 to 25 mg of material was placed in a platinum dish. The temperature was equilibrated at 50 °C for 10 min, followed by heating to 950 °C at a rate of 20 °C / min under nitrogen. The weight loss (WCO2) between approximately 550 °C and 700 °C was attributed to CO2 released from CaCO3; therefore, the chalk content was assessed as follows:
[0312] Chalk content = 100 / 44 × WCO2
[0313] The temperature was then reduced to 300°C at a cooling rate of 20°C / min. The gas was then switched to oxygen, and the temperature was raised again to 900°C. The weight loss in this step is attributed to carbon black (Wcb). Given the carbon black and chalk content, the ash content excluding chalk and carbon black is calculated as follows:
[0314] Ash content = (ash residue) - 56 / 44 × WCO2 - Wcb
[0315] The ash residue is the weight measured at 850°C during the first step under nitrogen atmosphere.
[0316] CIELAB
[0317] This method is used to measure the color of thin films and conforms to ISO 11664-4. Three standard color values, namely values X, Y, and Z, are measured using a spectrophotometer, and CIE L*, a*, b*, and their color differences are calculated using these values.
[0318] Optical performance
[0319] Total transmittance, diffuse transmittance, and haze are measured according to ASTM D1003-21 (Method A - Haze Meter). Sharpness is measured using the same instrument and principle as for haze, but at an angle less than 2.5° relative to the normal. When measuring sharpness, the sample is placed in the "Sharpness Port." The measurement is performed as follows:
[0320] Equipment: Haze Gard Plus
[0321] Manufacturer: BYK-Gardner GmbH
[0322] Model: 4725
[0323] • C light source
[0324] condition:
[0325] Adjustment time: >96 hours
[0326] Temperature: 23℃
[0327] • Test procedure: A-Hydrometer
[0328] gloss
[0329] Gloss is measured at a 45° angle according to ASTM D2457.
[0330] Optical defects
[0331] 100 µm films were produced using an ME25 / 5800 V3 extruder. The production line was equipped with a 25 mm extruder with a length of 25 / LD. The cast film production line was equipped with a standard cooling roller unit, a line scan camera for defect detection, and a tension-controlled film winding machine.
[0332] The goal is to produce a uniform film using constant melt pressure and temperature. Each test requires a 5 m... 2 The membrane undergoes standardized measurements. Once the area is reached, the measurement automatically ends, and the OCS software automatically generates the recorded values.
[0333] The number of defects measured in reflection mode is 1 / m 2 Based on this, it can be divided into size levels and multiplied by weighting factors to obtain the "category" index.
[0334] (Category) indices (such as the gel index) are automatically calculated using the following formula:
[0335] Size class 1: 100 µm to 299 µm. Weighting factor: ×0.1
[0336] Size class 2: 300 µm to 599 µm. Weighting factor: ×1.0
[0337] Size class 3, 600 µm to 1000 µm. Weighting factor: ×5.0
[0338] Size Class 4 >1000 µm Weighting Factor: ×10.0
[0339] This calculation can also be applied to each of the recorded categories (gels, other defects).
[0340] To obtain an overall overview of all membrane defects, the numbers of all defects are summed (combined defects = gelation + other defects). Alternatively, an index of the corresponding category can be used for calculation (combined defect index = gelation index + other defect index).
[0341] Description of gel and other defects:
[0342] gel
[0343] Gels are defined as defects that appear different from the surrounding membrane but are the same color as the surrounding film. They are often used to characterize native materials.
[0344] Other defects
[0345] Defects that are not commonly found in native materials. Examples include:
[0346] - Yellow oxidized polymer;
[0347] - Severely degraded black or brown polymers;
[0348] - Foreign particles of other polymer types (product contamination);
[0349] - And foreign objects such as metal shavings, wood chips, and paper;
[0350] - V-gel: Located in the extrusion direction; small V-shaped defects, usually caused by degraded fine particles;
[0351] - Filaments: Long, thin defects, usually oriented directly along the extrusion direction;
[0352] - Non-uniformity: mainly caused by the dependence between different MFR regions and the low energy input of the extruder.
[0353] X-ray computed tomography (XCT)
[0354] X-ray computed tomography (CT) was performed using a Thermo Fisher Scientific Heliscan MK2 instrument. The delivered pellets were scanned in a cylindrical sample holder. The voxel size was set to 4 µm. The X-ray tube operated with a LaB6 filament, a voltage set to 60 kV, a medium focal size, and a 0.1 mm thick steel pre-filter. The sample was scanned using a space-filling trajectory. For reconstruction, the offset and scaling values used to convert the 32-bit data to the final 16-bit data were fixed throughout all scans to allow for comparison of multiple sets of data.
[0355] Scan discs, each 5 mm in diameter and 500 µm thick, made of different polymers, together with the sample in a single scan. Discs made of at least one PP grade and one PET grade must be scanned.
[0356] Data analysis was performed using Avizo software (Thermo Fisher Scientific) for industrial testing. Gray values were determined from PP and PET discs and used as a guide for threshold setting. Using a threshold 72% lower than the gray value of PP, the sample data were segmented into polymer and air to determine the total volume.
[0357] The sample data were segmented using a grayscale threshold 11% higher than that of PET to obtain the fractionation of high-density particulate contaminants. This was taken into account that the density of PP is 0.905 g / cm³. 3 And the density of PET is 1.38 g / cm³. 3 This threshold corresponds to 1.53 g / cm³. 3 The density.
[0358] A second analysis was performed using a lower threshold to obtain a fraction of low-density particulate contaminants. The peak gray value of the particles was then determined against this threshold. A threshold 26% higher than the polymer peak value was used. All inclusions with gray values higher than the threshold used in the first analysis, representing high-density particulate contaminants, were subtracted from this fractionation result.
[0359] The particles are segmented into individual objects using a connected component filter. The minimum object size is set to 5 voxels. For each object, features such as average gray value, location, volume, length, width, and thickness are determined.
[0360] 2. Example
[0361] 2.1. Preparation of virgin polypropylene (v-PP1 and v-PP2)
[0362] The catalyst used to prepare v-PP1 is the Ziegler-Natta catalyst used in the embodiments of the invention WO 2016 / 066446 A1. Dicyclopentyldimethoxysilane (donor D) is used as the external donor, and triethylaluminum (TEAL) is used as the co-catalyst.
[0363] The polymerization conditions for v-PP1 are shown in Table 1 below.
[0364] Table 1 Polymerization conditions for virgin polypropylene (v-PP1)
[0365]
[0366] On a ZSK 18 twin-screw extruder, polymer powder obtained from v-PP1 was compounded with 371 ppm Irganox 1010 (produced by BASF), 741 ppm Irgafos 168 (supplied by BASF), 320 ppm Trigonox 101 (supplied by Nouryon), and 588 ppm Ceasit AV / T (supplied by Baerlocher) at a melt temperature of 210°C and a production rate of 7 kg / h.
[0367] Virgin polypropylene v-PP2 was produced in a Borstar pilot plant using a prepolymer-loop configuration and commercially available catalyst Avant ZN180 (LyondellBasell). Catalyst conditions were: TEAL 150 g / t propylene, donor 10 g / t propylene, catalyst feed rate 1.5 g / h. Loop pressure was 35 bar, temperature was 75°C, and H2 feed was 1100 ppm. Subsequently, the resulting powder was compounded with 333 ppm Irganox 1010 (supplied by BASF), 667 ppm Irgafos 168 (supplied by BASF), and 300 ppm DHT-4V (supplied by Kisuma / Kyowa) on a ZSK 18 twin-screw extruder at a melt temperature of 210°C and a production rate of 7 kg / h. The final MFR of the pellets was 8 g / 10 min.
[0368] 2.2 Blended Plastic Polypropylene Blends (B)
[0369] The following recycled stream was used as a precursor recycled stream to generate a mixed plastic polypropylene blend (B):
[0370] A1 can be obtained as a post-consumer flexible polypropylene waste stream as a byproduct of bottle recycling processes.
[0371] A2 German post-consumer plastic waste stream conforming to DSD323-2 specifications.
[0372] A3 Swedish post-consumer plastic waste stream enriched with post-consumer flexible PP products.
[0373] For B1, the following procedure is used (this procedure uses a precursor recycled stream that actually contains at least 85% by weight of polypropylene-labeled material):
[0374] Step 1: The precursor A1 was washed for 20 minutes in a single wash at 80°C using an aqueous washing solution containing 3.0 wt% NaOH and 0.30 wt% TubiWash EYE detergent. The material with a density different from that of polypropylene was then separated and removed by hydrocyclone.
[0375] Step 2: Use an air classifier to separate the product from Step 1 into heavy fractions (i.e., rigid components) and light fractions (i.e., flexible components).
[0376] Step 3: The light fraction from Step 2 is melt-extruded using an extruder equipped with dual filtration (using a laser filter as the first filter and a screen changer as the second filter. The laser filter has through-holes with a truncated conical cross-section, each with a small diameter of 90 µm and a large diameter of 110 µm. The screen changer has a filtration accuracy of 100 µm) to form a recycled polypropylene grade.
[0377] For B2 to B5 (which use precursor recycled streams that do not contain at least 85% by weight of polypropylene-labeled reclaimed feedstock), follow General Procedure A:
[0378] Step 1: Sort the precursor recovery stream by color (the criteria for this sorting step vary depending on the experiment, see below);
[0379] Step 2: First, wash the sorted product from Step 1 in a low-temperature alkaline washing step, and then wash it in a high-temperature alkaline washing step.
[0380] Step 3: Use an air separator to further separate the washed product from Step 2 into heavy fraction (i.e., rigid objects) and light fraction (i.e., flexible objects), discarding the light fraction and retaining the heavy fraction;
[0381] Step 4: Melt extrusion is performed on the sorted product from Step 3 to form a recycled polypropylene grade.
[0382] B2 involves subjecting precursor A2 to general procedure A, in which step 1 is omitted. B2 roughly corresponds to the r-PP membrane in Waste Management 153 (2022) 41-51.
[0383] B3 involves subjecting precursor A2 to general procedure A, in which step 1 only sorts colored objects (i.e., removes transparent objects).
[0384] B4 involves subjecting precursor A2 to general procedure A, wherein step 1 only sorts colored objects (i.e., removes transparent objects), and step 4 further includes a double melt filtration step (as described in step 3 regarding the preparation of B1).
[0385] B5 involves subjecting precursor A3 to general procedure A, in which step 1 sorts transparent objects (i.e., removes colored objects).
[0386] (Note: Since the precursor recycled stream A1 does not contain a significant amount of pigmented polypropylene (i.e., pigment dispersed in the polypropylene matrix, rather than ink on the surface), the preparation of B1 does not require a color sorting step (i.e. step 1 of general procedure A)).
[0387] The properties of various mixed plastic polypropylene blends (B) are shown in Table 2.
[0388] Table 2 Properties of the polypropylene blend of the present invention and the comparative blend (B)
[0389]
[0390] # - Due to the low amount of SF, it is impossible to accurately determine iV(SF) and C2(SF).
[0391] ## - No clearly visible peaks in the XRF spectrum
[0392] ### - LOD = Limit of Detection
[0393] 2.3 Preparation of the membrane, comparison membrane, and reference membrane of the present invention
[0394] Based on the formulations shown in Table 3, the compositions of the present invention and the comparative compositions were prepared by compounding in a Coperion ZSK 40 co-rotating twin-screw extruder at 220°C.
[0395] Prior to conversion, the recycled polypropylene granules of compositions B1, B2, B3, B4 and B5 were dried at 90°C for 4 hours.
[0396] A 50 µm cast film was prepared from the composition using the Collin laboratory-scale cast film production line. The ash residue of v-PP1 was negligible; therefore, the ash residues of IE2, CE4, and CE5 were taken as 35% of the corresponding values of their respective recycled materials B1, B4, and B5.
[0397] Table 3 Formulations and properties of the reference composition, comparative composition, and composition of the present invention.
[0398]
[0399] As shown in Table 3, despite the higher inorganic residue content, IE2 exhibits mechanical properties comparable to CE4 and CE5. Furthermore, IE2's optical properties are slightly superior to CE4 and CE5, which is particularly surprising considering its higher inorganic residue content. Additionally, Figures 1 and 2 show that the IE2 film has a superior appearance, both when viewed through photographs (Figure 1) and copier scans (Figure 2). To generate Figures 1 and 2, text (BOREALIS) was printed on paper, and a 50 µm cast film was placed on top of the printed text. IE2 clearly exhibits the best optical appearance, with the black spots on CE4 being particularly noticeable in Figure 2, while the black spots on CE5 are less pronounced.
Claims
1. A cast film comprising one or more layers, wherein, At least one of the one or more layers is composed of a polymer composition (PC), wherein the polymer composition (PC) comprises: a) 0.0% to 80.0% by weight of virgin propylene polymer (v-PP) relative to the total weight of the polymer composition (PC); and b) A blend of polypropylene (PPP) in the range of 20.0% to 100.0% by weight relative to the total weight of the polymer composition (PC), the blend of polypropylene (PPP) having a melt flow rate (MFR2) in the range of 3.5 g / 10 min to 10.0 g / 10 min as determined according to ISO 1133 at 230 °C and 2.16 kg, wherein the polymer portion of the blend of polypropylene (PPP) has: i) Ethylene content (C2(total)) in the range of 0.0 wt% to 5.0 wt% as determined by CRYSTEX QC analysis; ii) The content of crystal fraction (CF) in the range of 93.0% to 100.0% by weight as determined by CRYSTEX QC analysis; iii) The content of soluble fraction (SF) in the range of 0.0 wt% to 7.0 wt%, as determined by CRYSTEX QC analysis; and iv) Ethylene content (C2(CF)) of the crystal fraction in the range of 0.0 wt% to 5.0 wt%, as determined by CRYSTEX QC analysis.
2. The cast film according to claim 1, wherein, The virgin propylene polymer (v-PP) is a propylene homopolymer (h-PP) or a multiphase propylene copolymer (HECO), more preferably a multiphase propylene-ethylene copolymer (HECO).
3. The cast film according to claim 2, wherein, The virgin propylene polymer (v-PP) is a multiphase propylene-ethylene copolymer (HECO) having one or more, preferably all of, the following properties: a) Melt flow rate (MFR2) in the range of 1.0 g / 10 min to 10.0 g / 10 min, determined according to ISO 1133 at 230 °C and 2.16 kg. b) The content of soluble fraction (SF) in the range of 10.0% to 25.0% by weight and the content of crystallization fraction (CF) in the range of 75.0% to 90.0% by weight, as determined by CRYSTEX QC analysis; c) Ethylene content (C2(total)) ranging from 4.0 wt% to 10.0 wt% as determined by CRYSTEX QC analysis. d) Ethylene content (C2(CF)) of the crystallization fraction in the range of 1.0 wt% to 5.0 wt%, as determined by CRYSTEX QC analysis. e) Ethylene content (C2(SF)) of the soluble fraction in the range of 20.0 wt% to 40.0 wt%, as determined by CRYSTEX QC analysis. f) Intrinsic viscosity (iV(total)) in the range of 1.20 dL / g to 3.00 dL / g as determined by CRYSTEX QC analysis; g) The intrinsic viscosity (iV(CF)) of the said crystalline fraction in the range of 1.20 dL / g to 3.00 dL / g, as determined by CRYSTEX QC analysis; and h) The intrinsic viscosity (iV(SF)) of the soluble fraction in the range of 1.00 dL / g to 2.50 dL / g, as determined by CRYSTEX QC analysis.
4. The cast film according to any one of the preceding claims, wherein, At least 90% by weight, more preferably at least 95% by weight, and even more preferably at least 98% by weight of the mixed plastic polypropylene blend (B) is derived from recycled materials.
5. The cast film according to claim 4, wherein, The recycled material is derived from labels containing polypropylene by at least 85% by weight.
6. The cast film according to any one of the preceding claims, wherein: a) Relative to the total weight of the mixed plastic polypropylene blend (B), the mixed plastic polypropylene blend (B) has an inorganic residue (ash residue) content in the range of 0.10 wt% to 7.5 wt%, more preferably 1.0 wt% to 5.0 wt%, and most preferably 2.0 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA); and / or b) The polymer composition (PC) has an inorganic residue (ash residue) content in the range of 0.10% to 7.5% by weight, more preferably 0.30% to 5.0% by weight, and most preferably 0.50% to 4.0% by weight, as determined by thermogravimetric analysis (TGA).
7. The cast film according to any one of the preceding claims, wherein, The mixed plastic polypropylene blend (B) has: a) A total combined defect index value in the range of 4,000 to 35,000, more preferably 8,000 to 30,000, and most preferably 10,000 to 25,000, determined according to the method given in the determination method; and / or b) The number of combined defects in the range of 20,000 to 200,000, more preferably 30,000 to 180,000, and most preferably 40,000 to 150,000, as determined by the method given in the determination method.
8. The cast film according to any one of the preceding claims, wherein, The mixed plastic polypropylene blend (B) has: a) An aluminum (Al) content of at least 60 ppm as determined by X-ray fluorescence spectrometry (XRF); and / or at least three, more preferably all, of the following properties: b) An iron (Fe) content of at least 30 ppm as determined by X-ray fluorescence spectrometry (XRF); c) A sodium (Na) content of at least 30 ppm as determined by X-ray fluorescence spectrometry (XRF); d) A sulfur (S) content of at least 5 ppm as determined by X-ray fluorescence spectrometry (XRF); and e) A zinc (Zn) content of at least 25 ppm as determined by X-ray fluorescence spectroscopy (XRF).
9. The cast film according to any one of the preceding claims, wherein, The mixed plastic polypropylene blend (B) has a total volatile organic compound (TVOC) in the range of 0 µg / g to 25 µg / g, more preferably 0 µg / g to 18 µg / g, and most preferably 0 µg / g to 15 µg / g, as determined according to the measurement method given in the determination method.
10. The cast film according to any one of the preceding claims, wherein, The polymer composition (PC) comprises, more preferably, the following components: a) The virgin propylene polymer (v-PP) in the range of 0.0% to 70.0% by weight relative to the total weight of the polymer composition (PC). b) The mixed plastic polypropylene blend (B) in the range of 30.0% to 100.0% by weight relative to the total weight of the polymer composition (PC). c) Optionally, other polymeric components (P) ranging from 0.0% to 10.0% by weight relative to the total weight of the polymeric composition (PC); and d) Optionally, an additive (A) in the range of 0.0% to 5.0% by weight relative to the total weight of the polymer composition (PC).
11. The cast film according to any one of the preceding claims has a thickness in the range of 10 µm to 200 µm, more preferably 20 µm to 100 µm, and most preferably 30 µm to 80 µm.
12. The cast film according to any one of the preceding claims has one or more, preferably all of, the following properties: a) Total transmittance in the range of 70% to 100% as determined by ASTM D1003; b) Sharpness values within the range of 40% to 80% as determined by ASTM D1003; c) Haze values within the range of 20% to 80% as determined by ASTM D1003; d) Longitudinal (MD) 45° gloss value within the range of 20.0 to 35.0 as determined by ASTM D2457; and e) Transverse (TD) 45° gloss value in the range of 18.0 to 30.0 as determined by ASTM D2457.
13. The cast film according to any one of the preceding claims, wherein: a) The polymer composition has an inorganic residue (ash residue) content in the range of 1.0 wt% to 5.0 wt%, most preferably 2.0 wt% to 4.0 wt%, as determined by thermogravimetric analysis (TGA), relative to the total weight of the polymer composition (PC); b) The cast film has a thickness in the range of 20 µm to 100 µm, most preferably 30 µm to 80 µm; and c) The cast film has a haze value in the range of 20% to 80%, more preferably 30% to 70%, and most preferably 40% to 60% as determined by ASTM D1003.
14. The cast film according to any one of the preceding claims is a single-layer film.
15. The cast film according to any one of claims 1 to 13, wherein, The core layer is composed of a polymer composition (PC) as defined in any one of claims 1 to 10.
Citation Information
Patent Citations
Heterophasic polypropylene with improved stiffness / impact balance
WO2016066446A1
